Development of Tablet Device App for Parkinson’s Disease Patients’ Continuous Self-Monitoring and Management - Kim, Bona; Baldwin, Jeff; Lukasiewicz, Kara; Hallett, Mark; Harrington, John; Altemus, Anne; Lungu, Codrin (Neuroscience and Biomedical Engineering (Discontinued), 2015)
Clinical data collection in Parkinson’s disease (PD) patients is typically limited to twice or thrice yearly visits with the neurologist. This creates potential for recollection bias and difficulty assessing disease severity and response to medication. We sought to develop a patient-driven mobile app that optimizes PD patient-reported outcome collection. We observed what health topics dominated discussion during appointments between patients and their neurologists. We assessed how often specific health events were included in the neurological history form filled out before the patients’ appointments, how PD patients described symptom changes, and if PD patients kept a detailed account of their health events. We created an interactive prototype of an iPad app designed with specific patient physical and cognitive challenges in mind that would help PD patients keep detailed records of daily health status. PD patients, caregivers, and neurologists tested the prototype app, and iterative design changes were made based on their feedback. The app features a cognitively simple user interface that requires little instruction, an analog scale with graphical presentation for documenting slowness, tremor, walking/balance, dyskinesia, mood, speech and additional video/audio input that can provide neurologists with objective accounts of PD patients’ health condition. We interviewed PD patients who participated in the initial pilot to evaluate usability of this app in a PD population. The pilot demonstrated that an iPad-based app was easy to use. PD patient testing of the iPad app is ongoing. Once the study is completed, several validity measures will be assessed by independent interviews with patients and providers.
Keywords: Mobile application